Implementing Decentralized Local Governance: A Treacherous Road with Potholes, Detours, and Road Closures - Shah, Anwar; Thompson, Theresa (World Bank, Washington, D.C., 2013)
During the past two decades, a silent revolution in public sector governance has swept across the globe aiming to move decision making for local public services closer to the people. The countries embracing and adapting to this silent revolution have had diverse motives and followed even more diverse approaches. This paper attempts to present a stylized view of the motivations and approaches used to strengthen local governance. The quest for the right balance, i.e. appropriate division of powers among different levels of government, is not always the primary reason for decentralizing. There is evidence that the decentralization decision may have more to do with short-term political considerations than the long-run benefits of decentralization. To take stock of progress worldwide, we take a comparative look at developments in political, fiscal and administrative decentralization for a selected group of countries. Most of the decentralization literature deals with normative issues regarding the assignment of responsibilities among different levels of government and the design of fiscal transfers. The process of decentralization has not received the attention it deserves as the best laid plans can fail due to implementation difficulties. We revisit major controversies regarding preferred approaches to obtaining a successful outcome. Key approaches examined are big push versus small steps; bottom up vs. top down; and uniform vs. asymmetric decentralization. Finally, Indonesia's 1999 big bang decentralization program is evaluated. The program should be commended for its achievements over a short period of time, however incentives are lacking for local governments to be accountable and responsive to their residents.